The implementation of Islamic Education in shaping tolerant characters in multicultural perspective - Zaenuri Rofi'in (ATTARBIYAH: Journal of Islamic Culture and Education, 2018)
This study aimed to find out about the subject of Islamic Education which contains tolerant values, the implementation of Islamic Education in building the tolerant characters through multiculturalism perspective, and its impacts in SMPN 1 Kaloran and SMPN 2 Kaloran. The method used in the research was qualitative research, and case study for the approach. The subjects of this research were the head master, Islamic Education teacher, and also the students in SMPN 1 Kaloran and SMPN 2 Kaloran. For the data collection technique, I used observation, interview and documentation. Data analysis technique was descriptive in analyzing contents implementation and the impact of Islamic Education implementation in shaping the tolerance character through multiculturalism perspective in SMPN 1 Kaloran and SMPN 2 Kaloran. As the results of the research, the content of tolerant values of Islamic Education in SMPN 1 Kaloran and SMPN 2 Kaloran can be found in: core competence, based competence, syllabus, and instructional books. The implementation of Islamic Education in building the tolerant characters through multicultural perspective is realized in forms of extracurricular activities, Memorial Day’s commemoration, various habits at school and learning methods used. The impact of Islamic Education in shaping the student tolerant characters are the awareness of diversity and reductions of negative prejudices of other religion’s followers resulted in the realization of the student’s harmony, one another.